Importance of charge regulation in attractive double-layer forces between dissimilar surfaces - Popa, Ionel; Sinha, Prashant; Finessi, Marco; Maroni, Plinio; Papastavrou, Georg; Borkovec, Michal (Physical review letters, 2010)
Direct force measurements between oppositely charged latex particles in aqueous electrolyte solutions were carried out with a multiparticle colloidal probe technique based on atomic force microscopy. Force profiles between two dissimilarly charged surfaces can be only described when charge regulation effects are taken into account, while constant charge or constant potential boundary conditions are inappropriate. Surface potentials and regulation parameters are determined from force data obtained in symmetric systems with the Poisson-Boltzmann theory and constant regulation approximation. The resulting quantities are used to predict the force profiles in asymmetric systems, and good agreement between theory and experiment is found. These findings show that charge regulation is important to quantify double-layer forces in asymmetric systems.